ANALISIS PENYERAPAN TENAGA KERJA DI INDUSTRI KECIL KONVEKSI (Studi Kasus di Kelompok Usaha Bersama Konveksi Kabupaten Tulungagung) - Kurniawan, Mochamad Arif (Jurnal Ilmiah Mahasiswa FEB, 2018)
The role of small and medium industries is very important in the national economy as well as in the absorption of labor. Small and medium industries are able to accommodate unabsorbed workers and are excluded from work competition. According to the agreement of the Industry and Trade Office each Regency / City must have core competencies of each region, In Tulungangung District itself has been agreed that the core competence of the region is convection. With some predetermined variables, this study aims to: (1) To determine the effect of independent variables (capital, production value, education level, wages, length of business) on the dependent variable (employment absorption) in KUBE Convection Tulungagung District. (2) To know the most dominant factor in influencing the absorption of manpower on KUBE Tulungagung District Convection. Place and time of this research is on all Group of Together Convection Business of Tulungagung Regency in May 2017. Analytical method used is multiple linear regression. The results showed that capital, production value, education level, wage, and length of business have a positive and significant effect on labor absorption. Wages become the most dominant variable.Key Words : Manpower Absorption, capital, production value, education level, wages, length of business.